WISC-III Cognitive Profiles in Children with Developmental Dyslexia: Specific Cognitive Disability and Diagnostic Utility - Moura, Octávio (2014)
This study analysed the usefulness of the Wechsler Intelligence Scale for Children-Third Edition in identifying specific cognitive impairments that are linked to developmental dyslexia (DD) and the diagnostic utility of the most common profiles in a sample of 100 Portuguese children (50 dyslexic and 50 normal readers) between the ages of 8 and 12 years. Children with DD exhibited significantly lower scores in the Verbal Comprehension Index (except the Vocabulary subtest), Freedom from Distractibility Index (FDI) and Processing Speed Index subtests, with larger effect sizes than normal readers in Information, Arithmetic and Digit Span. The Verbal-Performance IQs discrepancies, Bannatyne pattern and the presence of FDI; Arithmetic, Coding, Information and Digit Span subtests (ACID) and Symbol Search, Coding, Arithmetic and Digit Span subtests (SCAD) profiles (full or partial) in the lowest subtests revealed a low diagnostic utility. However, the receiver operating characteristic curve and the optimal cut-off score analyses of the composite ACID; FDI and SCAD profiles scores showed moderate accuracy in correctly discriminating dyslexic readers from normal ones. These results suggested that in the context of a comprehensive assessment, the Wechsler Intelligence Scale for Children-Third Edition provides some useful information about the presence of specific cognitive disabilities in DD. Practitioner Points. Children with developmental dyslexia revealed significant deficits in the Wechsler Intelligence Scale for Children-Third Edition subtests that rely on verbal abilities, processing speed and working memory. The composite Arithmetic, Coding, Information and Digit Span subtests (ACID); Freedom from Distractibility Index and Symbol Search, Coding, Arithmetic and Digit Span subtests (SCAD) profile scores showed moderate accuracy in correctly discriminating dyslexics from normal readers. Wechsler Intelligence Scale for Children-Third Edition may provide some useful information about the presence of specific cognitive disabilities in developmental dyslexia.